Interaction of the Transcription Start Site Core Region and Transcription Factor YY1 Determine Ascorbate Transporter SVCT2 Exon 1a Promoter Activity - Qiao, Huan; May, James M. (PLOS ONE, 2012)
Transcription of the ascorbate transporter, SVCT2, is driven by two distinct promoters in exon 1 of the transporter sequence. The exon 1a promoter lacks a classical transcription start site and little is known about regulation of promoter activity in the transcription start site core (TSSC) region. Here we present evidence that the TSSC binds the multifunctional initiator-binding protein YY1. Electrophoresis shift assays using YY1 antibody showed that YY1 is present as one of two major complexes that specifically bind to the TSSC. The other complex contains the transcription factor NF-Y. Mutations in the TSSC that decreased YY1 binding also impaired the exon 1a promoter activity despite the presence of an upstream activating NF-Y/USF complex, suggesting that YY1 is involved in the regulation of the exon 1a transcription. Furthermore, YY1 interaction with NF-Y and/or USF synergistically enhanced the exon 1a promoter activity in transient transfections and co-activator p300 enhanced their synergistic activation. We propose that the TSSC plays a vital role in the exon 1a transcription and that this function is partially carried out by the transcription factor YY1. Moreover, co-activator p300 might be able to synergistically enhance the TSSC function via a “bridge” mechanism with upstream sequences.